„Diaspora diplomacy” – involvement of the diaspora in building the reputation of the state in the international arena on the example of Turkey - Fraszka, Łukasz Sławomir (Free your mind: Reflections on language, literature and culture, 2022)
As a non-state actor in international relations, the diaspora has a strong influence on the society of the host state, but also on the state of origin. Therefore, the use of the diaspora has become a significant means of promoting the soft power of the state of origin. This paper seeks to understand the extent to which diasporas are independent actors and the extent to which their position in the different contexts of host and home states affects their political activity. The pursuit of influence by building networks, communicating persuasive narratives, setting international rules, and using (soft) resources have become major state activities in the international arena. Accordingly, states have been forced to use new tools to build their reputations in the international arena. One such tool has become „diaspora diplomacy”, a state action to use the diaspora to promote a positive image of the country of origin as well as its culture in the host country. The diaspora is not only a foreign policy tool, but as an element of soft power, it can exert pressure on the country of origin. Therefore, diaspora communities can influence the economic and political processes of host countries in favor of the interests of their homelands. One country that has begun to focus on developing its influence by „diaspora diplomacy” is Turkey under the Justice and Development Party government.